Blood glucose and insulin levels in patients with peripheral vestibular disease - Serra,Ana Paula (2009)
Metabolic disorders can cause dizziness. AIM: to study the prevalence of glucose and glucose-insulin alterations in patients with peripheral vestibular disorders by studying the four-hour glucose-insulin curve; to check at what time there was the highest prevalence of altered cases and whether the glucose and insulin curves together are better than the isolate glucose curve and fasting glucose curve. MATERIALS AND METHODS: retrospective study, analyzing 81 four-hour glucose-insulin curves in patients with peripheral vestibular dizziness. RESULTS: Four-hour glucose-insulin curve alterations happened in 87.7% of the patients. Hypoglycemia was seen in 61.7% of the cases, hyperinsulinemia in 55.5%, hyperglycemia in 27.2%, glucose intolerance in 12.3% and hypoinsulinemia in 1.2%. Normal tests were seen in 12.3 % of the cases and altered fasting glucose in 23.5%. CONCLUSIONS: The four-hour glucose-insulin curve analysis showed that 87.7% of the patients with dizziness and suspicion of peripheral vestibular disorder had glucose or insulin metabolism disorders. The highest number of alterations was seen up to the third and fourth hour of the glucose-insulin curve. The glucose and insulin curves together overcame the glucose curve alone and fasting glucose curve in regards of the prevalence of altered cases.